Increased erythrocyte superoxide dismutase activities in beta 0-thalassaemia/haemoglobin E and in haemoglobin H diseases. - Yenchitsomanus, P (1983)
Erythrocyte superoxide dismutase activities were measured in 45 subjects, 15 each of beta 0-thalassaemia/haemoglobin (Hb) E disease, Hb H disease, and normal. The erythrocyte superoxide dismutase activities were significantly higher in the patients with beta 0-thalassaemia/Hb E and Hb H diseases than in the normal subjects. The increase of erythrocyte superoxide dismutase activities is most likely due to abnormalities specific to thalassaemic red cells rather than an increased number of younger red cells for reticulocytes and nucleated red blood cells did not affect the enzyme activity. Patients with beta 0-thalassaemia/Hb E disease with lower haemoglobin concentration had significantly higher superoxide dismutase activities. In all 45 subjects haemoglobin concentrations and superoxide dismutase activities were inversely correlated (r = -0.60 (p less than 0.001)). This indicates that the amounts of superoxide generated in the red cells may, at least partly, determine severity of red cell damage and thus severity of disease; the increased superoxide dismutase activity in thalassaemia is a response to superoxide generated in greater amounts because of accumulation of excessive globin chains and iron in the red cells. The superoxide dismutase activities in Hb H disease, an alpha-thalassaemic disease, were found to be strikingly increased, higher than in beta 0-thalassaemic disease or other conditions.